T-shaped linear-stapled cervical esophagogastric anastomosis for minimally invasive esophagectomy: a pilot study. Issue 6 (December 2020) - Li, Xinju; Wang, Zhe; Zhang, Guangjian; Fu, Junke; Wu, Qifei
Background: Minimally invasive esophagectomy (MIE) has become a good option in the surgical treatment of esophageal cancer. Cervical esophagogastric anastomoses (CEGA) are widely used during esophagectomy. However, CEGA are related with a higher incidence of anastomotic complications. In the present study, a new procedure of T-shaped linear-stapled cervical esophagogastric anastomosis was used during MIE and the short-term outcomes are presented. Methods: From May 2014 to December 2018, 32 consecutive patients with esophageal cancer who underwent total MIE followed by T-shaped linear-stapled cervical esophagogastric anastomosis were included. Postoperative outcomes were analyzed. Results: Fifteen men and 17 women were included this pilot study. The histology of all cases was squamous cell carcinoma. Mean operation time of T-shaped linear-stapled cervical esophagogastric anastomosis was 17.6 minutes. There were no early or late mortalities. A minor cervical anastomotic leakage occurred in 1 patient. No complications of anastomotic stenosis occurred in this study. Conclusion: The T-shaped linear-stapled cervical esophagogastric anastomosis is efficient, reliable, easy to perform, and associated with lower postoperative complication rate.